ANALYSIS ROLE OF BANGKIT MERBABU FARMING GROUP TOWARDS ORGANIC VEGETABLE AGRICULTURAL SOP APPLICATION IN DESA BATUR GETASAN DISTRICT - Tarihoran, Ria Kristin Gustina Br; Gayatri, Siwi; Mariyono, Joko (Universitas Galuh, 2024)
The role of farmer groups as a learning class, a cooperation vehicle, and a production unit in the implementation of organic vegetable farming is important to produce quality and safe-to-consume products. This research aims to describe the role of the Bangkit Merbabu Farmer Group, describe the implementation of organic farming SOP by the Bangkit Merbabu Farmer Group, and analyze the influence of farmer group roles on the implementation of organic vegetable farming SOPs. The study was conducted from November 6 to December 28, 2023. The research location was the Bangkit Merbabu Farmer Group located in Kaliduren Hamlet, Batur Village, Getasan Sub-district, Semarang Regency, Central Java. The research method used was a census method with saturated sampling involving all 53 members of the Bangkit Merbabu Farmer Group. The analysis methods used were quantitative descriptive and multiple linear regression analysis. The research shows that the Bangkit Merbabu Farmer Group has characteristics such as: the average age of members is 19-59 years old, the majority have only completed elementary education, and farming is their primary occupation. The results of this research indicate that the role of farmer groups as a learning class, a cooperation vehicle, and a production unit falls into the good category with percentages of 58%, 53%, and 60% for the production unit falling into the rare category. The implementation of organic vegetable farming SOPs has a percentage of 49% and falls into the rare category. Based on the SPSS output results in multiple linear regression analysis, the learning class, cooperation vehicle, and production unit have simultaneous effects on the implementation of organic vegetable farming SOP. The factors from the independent variables contribute 39.6%, while the rest is influenced by other factors. Based on the t-test, there is a significant influence for the role of the learning class and cooperation vehicle, while there is no influence for the production unit.